Patterns of knowledge use in 'low-tech' industries. (1st March 2015) - Hirsch-Kreinsen, Hartmut
Abstract : The innovativeness of low- and medium-technology (LMT) manufacturing firms in advanced economies has been the research focus of a growing body of literature since the beginning of the last decade. This paper reviews the main research findings and highlights the largely unresolved problem in LMT research of the contradiction between the presumed homogeneity of LMT sectors because of the formal category of 'low R&D intensity', and the heterogeneity of the same firms in LMT sectors. To overcome this problem, the paper proposes an empirical taxonomy of innovative LMT firms based on the dimension of knowledge. To sketch out this knowledge-oriented taxonomy, the paper uses the concept of the 'distributed knowledge base'. In this approach, four different patterns of knowledge use in LMT firms can be identified. This conceptual perspective has consequences for understanding the sources and directions of innovation strategies in LMT firms and the perspectives of LMT sectors pertaining in advanced economies, such as the EU. Additionally, specific recommendations on innovation policy can be inferred from these considerations that go beyond the current state of the art. Overall, this paper sums up some of the findings of past low-tech research, and reinterprets its central findings.